A strategy dedicated to the concise and efficient development of the customized large-signal model for GaAs HEMTs. Issue 1 (1st June 2022) - Zhu, Huabing; Yan, Zhihai; Tian, Weiqian; Zhao, Hong; Song, Cheng; Zhang, Lin; Hu, Bin
Abstract: In this letter, a strategy dedicated to the concise and efficient development of the customized large-signal models for GaAs HEMTs is proposed, which is specialized for MMIC designers. The core concepts of the strategy are a deconstruction of the original thought of model construction and dimension reduction of the objective functions of optimization algorithms. The development of an Angelov-based customized large-signal model following this strategy has been successfully applied to GaAs HEMTs in 70nm process. The results show that it takes less than five minutes to execute such a parameter extraction algorithm with a one-button extraction function and good agreement is achieved between the model simulation and device measurement up to 65GHz.